Qualitative and Quantitative Analysis of Extract of Aerial Parts Of Ziziphus Mauritiana - Siddiqui, Suboohi; Saxena, Jyoti (Journal of Neonatal Surgery, 2025)
The present study investigates the extraction, phytochemical composition, and in vitro antimicrobial activity of the hydroalcoholic extract of the aerial parts of Ziziphus mauritiana. The extraction yielded a higher percentage with hydroalcoholic solvent (6.30%) compared to petroleum ether (1.25%). Phytochemical screening revealed the presence of alkaloids, flavonoids, phenols, proteins, carbohydrates, saponins, and tannins in the hydroalcoholic extract, while the petroleum ether extract was limited to carbohydrates. The quantification of bioactive compounds showed that the hydroalcoholic extract contained significant amounts of phenols (0.90 mg/100 mg), flavonoids (1.16 mg/100 mg), and alkaloids (1.64 mg/100 mg). The diverse range of bioactive compounds supports the extract's antimicrobial, antioxidant, and anti-inflammatory properties. These findings suggest that the hydroalcoholic extract of Ziziphus mauritiana has substantial potential for the development of therapeutic agents, especially for treating microbial infections.